2013
DOI: 10.1111/jan.12110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the expectations, needs and experiences of general practitioners and nurses towards a proactive and structured care programme for frail older patients: a mixed‐methods study

Abstract: This explanatory mixed-methods study showed that general practitioners and practice nurses perceived the U-CARE programme as feasible in general practice. A transition was made from reactive, ad hoc care towards a proactive and preventive care approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(103 citation statements)
references
References 31 publications
(48 reference statements)
3
97
0
1
Order By: Relevance
“…This theme was informed by nine studies [33,36,39,45,49,50,61,63,68] and includes examples of experiences and opinions which challenge or support the notion that frailty development is malleable. While health professionals showed confidence in prevention and management of frailty, they also acknowledged the difficulty of having the right tools to identify people who might benefit, and when intervention would be more useful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This theme was informed by nine studies [33,36,39,45,49,50,61,63,68] and includes examples of experiences and opinions which challenge or support the notion that frailty development is malleable. While health professionals showed confidence in prevention and management of frailty, they also acknowledged the difficulty of having the right tools to identify people who might benefit, and when intervention would be more useful.…”
Section: Resultsmentioning
confidence: 99%
“…Twentysix papers contributed to this theme [3136,3840,43,46,47,5258,60,62,65,7072,74]. This theme presents findings related to care providers’ capacity to care, taking a patient-centred and family-centred approach to care.…”
Section: Resultsmentioning
confidence: 99%
“…Health care providers cite insufficient time and limited financial resources as barriers to proactive, goal based care, particularly for older adults with multiple morbidities (Bleijenberg et al, 2013). Discharge planners and community service providers reported that disabilities and deficits remain the central focus with insufficient attention to older adults’ goals when transitioning from hospital to home setting.…”
Section: Background and Significancementioning
confidence: 99%
“…Uit de evaluatie bleek dat ouderen die het programma ontvingen meer behoud van zelfredzaamheid hadden dan ouderen die het traditionele zorgaanbod ontvingen [7]. Bovendien werd het zorgprogramma positief ontvangen door ouderen en hun mantelzorgers, huisartsen en praktijkverpleegkundigen [8,9]. Mede hierdoor waren verschillende huisartsenpraktijken in de regio gemotiveerd om het programma in de praktijk te implementeren.…”
Section: Inleidingunclassified